Diagnostic Efficacy of Combined N-Terminal Pro-Brain Natriuretic Peptide (NT-proBNP) and Cardiac Troponin I (cTnI) Testing in Myocardial Injury of Children with Mycoplasma Pneumoniae Pneumonia - Yang M; Xuan A; Zhu G (Journal of Multidisciplinary Healthcare, 2025)
Mei Yang,1 Aili Xuan,1 Guoji Zhu2 1Department of Pediatrics, First Affiliated Hospital of Bengbu Medical University, Anhui, People’s Republic of China; 2Department of Infectious Diseases, Children’s Hospital, Soochow University, Jiangsu, People’s Republic of ChinaCorrespondence: Guoji Zhu, Email zutt681@163.comObjective: To evaluate the diagnostic performance of combined N-terminal pro-brain natriuretic peptide (NT-proBNP) and cardiac troponin I (cTnI) testing for myocardial injury in children with Mycoplasma pneumoniae pneumonia (MPP).Methods: This retrospective study included 103 pediatric patients with MPP complicated by myocardial injury admitted between December 2021 and December 2023. Patients were stratified by New York Heart Association (NYHA) functional class (I–IV). Demographic and clinical characteristics, biomarker levels, and diagnostic accuracy were analyzed. ROC curves were used to assess diagnostic performance of single and combined biomarkers.Results: No significant differences were observed in age or gender across NYHA classes. However, BMI Z-scores declined significantly with worsening class (P = 0.013), while heart rate, systolic blood pressure, fever duration, respiratory rate, and hospital stay increased progressively (all P < 0.01), indicating disease severity. Serum NT-proBNP and cTnI levels rose in parallel with advancing NYHA class (P < 0.001 between all adjacent groups). A strong positive correlation was found between NT-proBNP and cTnI (r = 0.617, P < 0.001). Combined biomarker testing demonstrated superior diagnostic accuracy (AUC = 0.914), outperforming NT-proBNP (AUC = 0.877) and cTnI alone (AUC = 0.739). The combination improved sensitivity (94.15%) and specificity (95.19%), reducing false negatives and enhancing risk stratification. Notably, 80% of NYHA class III–IV cases were correctly reclassified into the high-risk group, with a net reclassification improvement (NRI) of +34.2% (P = 0.002).Conclusion: Combined NT-proBNP and cTnI testing provides robust diagnostic efficacy for myocardial injury in pediatric MPP. This dual-biomarker strategy enables earlier identification of high-risk patients and supports more precise clinical management.Keywords: NT-proBNP, cTnI, combined testing, children, mycoplasma pneumoniae pneumonia, myocardial injury, diagnostic efficacy, ROC